Impact of Cosmetic Camouflage on the Quality of Life of Children With Skin Disease and Their Families. Issue 3 (May 2016) - Salsberg, Jennifer M.; Weinstein, Miriam; Shear, Neil; Lee, Michelle; Pope, Elena
Background/Objectives: Cosmetic camouflage is known to improve quality of life in adults. Few data are available regarding cosmetic camouflage in children, and thus it is not often selected as a mode of treatment. We sought to determine whether cosmetic camouflage leads to improved quality of life of pediatric patients with visible dermatoses and their parent or primary caregiver. Methods: Patients aged 5 to 17 years with visible skin disease and their parent were assessed with the Children's Dermatology Life Quality Index (CDLQI) and the Family Dermatology Life Quality Index (FDLQI) before and after consultation regarding cosmetic camouflage. Results: Twenty-two children with skin conditions were included in the study. The mean CDLQI decreased from 6.82 (SD = 1.28) to 3.05 (SD = 0.65; P = .0014), while the mean FDLQI decreased from 7.68 (SD = 1.15) to 4.68 (SD = 0.92; P = .0012). Conclusions: Our study highlighted improvement in quality of life in patients with skin disorders who were managed with cosmetic camouflage.